Immunomodulatory Effects of Medicinal Plants used for Vitiligo in Traditional Persian Medicine - Ebrahimabadi, Mohsen H.; Lamardi, Seyede N. S.; Shirbeigi, Laila (Current Drug Discovery Technologies, 2021)
Background: Vitiligo is a hypopigmentation disorder that affects 1% of the world's population. Vitiligo causes white spots on the skin, mucous membranes, or white hair by destroying skin melanocytes. The pathogenesis of vitiligo is unknown but autoimmune, autocytotoxic, and neural mechanisms are suggested. According to the autoimmune theory, in people with vitiligo, immune cells invade and damage melanocytes. T cells are more commonly present in vitiligo patients' skin and remain in the lesion site, which is composed of CD8 and CD4 T cells. Many studies have been conducted on the presence and role of cytokines such as interleukins and interferongamma (IFN-γ) in the vitiligo process. Aim: This study aimed to introduce herbs effective against vitiligo from the perspective of Persian medicine and to investigate their possible therapeutic mechanisms with the possible effects of herbs on autoimmune mechanisms. Methods: For this purpose, keywords were used to extract data from Persian medicine textbooks, and then relevant scientific databases, including Google Scholar, PubMed, Web of Science, and Scopus were examined. Results: It was found that Persian medicine scholars used 50 different medicinal plants to treat and reduce the complications of vitiligo, and recent scientific studies have proven immune-regulating properties and reducing the effect of many of them on cytokines. Conclusion: According to scientific evidence on immunomodulatory effects, new research into the effects of these plants on vitiligo can lead to the discovery of new drugs and approaches for treating this disease.
Keywords: vitiligo